Analysis of factors related to the H Index of CNPq scientific productivity researchers in the field of Physical Education in Brazil - Diego Augusto Santos Silva; Carolina Fernandes da Silva (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aim: To verify the association between sociodemographic, academic background, professional performance, bibliographic production and training of human resources factors with the H Index of CNPq scientific productivity researchers in the field of Physical Education. Methods: This cross-sectional study included 94 researchers with scientific productivity grants (PQ) in the field of Physical Education in Brazil distributed into academic prestige level: PQ 1A-1D (n = 41) and PQ 2 (n = 53). For this, the H Index of these researchers was analyzed in the Scopus database. Related factors were sociodemographic, academic background, professional performance, bibliographic production, and training of human resources (student supervisor). Simple and multiple linear regression was used with a 5% significance level. Results: The H Index, number of citations, number of scientific articles in the last 10 years, number of books in the last 10 years, and the training of students at graduate levels of PQ 1A-1D was higher than that of PQ 2 (p <0.05). The H Index of PQ 1A-1D scholarship researchers was directly related to the number of scientific articles [H index = 8.48 + 0.11 * (Articles)]. The H index of PQ 2 scholarship researchers was directly related to the number of scientific articles and academic books and, inversely to the student supervision at master level [H index = 15.19 + 0.06 * (Articles) + 2.45 * (Books) - 0.34 * (Masters)]. Conclusion: H Index of researchers in the field of Physical Education in Brazil varied according to the academic recognition level.